A comparative study of post-hospital aphasic rehabilitative techniques (1998)
This study compared the performance of two categories of stroke-aphasic patients on the rehabilitative programmes exposed them to after the hospital treatment. Through a t-test statistic at the 0.05 alpha level we found significant differences in the performance of males and females, holistic and gestural rehabilitative strategies, fluent and non-fluent patients. The research findings revealed the mean values as (X = 7.3 4.5, t’obs = 6.2 :P 0.05); (X= 6.8/4.9; t’obs = 3.52; P 0.05); and (X = 6.4 /4.5; fobs = 3.40 ;P 0.05) respectively. Also, the results of the study showed that the holistic rehabilitative method performed better in the restoration of patients communicative skills. Finally, the paper gave some suggestions to be adopted in running a rewarding rehabilitative programmes.